Use of a Caprine Serum Fraction-Immunomodulator to Reduce Mortality in Commercial and Large-Bodied Turkey Lines Infected with Pasteurella multocida - Peebles, E.D.; Willeford, K.O.; Keirs, R.W.; Nestor, K.E.; Saif, Y.M.; Wang, C.; Matyi, C.J.; Anderson, J.W.; Kidd, M.T.; Pulikanti, R. (International Journal of Poultry Science, 2008)
The effectiveness of an injected caprine serum fraction-immunomodulator (CSF-I2) as an immunostimulant in male and female F-line and commercial turkey poults infected with fowl cholera (Pasteurella multocida) was examined in separate trials. In the first 2 of 3 controlled trials, the effects of an i.m. injection of CSF-I2 given 24 h prior to a P. multocida challenge, administered by s.c. injection, on mortality and days to death in F-line turkeys was determined. The CSF-I2 reduced mortality but did not affect average number of days to death of F-line turkeys across trials and sexes when administered 24h prior to a P. multocida challenge. In the third trial, the effects of an i.m. injection of CSF-I2 given to a commercial line of turkeys 24h prior to an s.c. injection of P. multocida on mortality and days to death were determined. While positive control commercial turkey poults experienced an 85% level of mortality across sex, the administration of CSF-I2 did not significantly reduce percentage mortality or average number of days to death. The difference in the effects of CSF-I2 on mortality in F-line and commercial turkey poults challenged with P. multocida suggests that CSF-I2 did not impart immunostimulation to commercial turkeys as it did in F-line turkeys that were infected with P. multocida. Therefore, genetic variation in turkeys may be an important consideration before using CSF-I2 as an immunomodulator to protect juvenile turkeys against fowl cholera.